Stage-Dependent Agreement between Cerebrospinal Fluid Proteins and FDG-PET Findings in Alzheimer's Disease - Yakushev, Igor; J. Muller, Matthias; Buchholz, Hans-Georg; Lang, Ulrike; Rossmann, Heidi; Hampel, Harald; Schreckenberger, Mathias; Fellgiebel, Andreas (Current Alzheimer Research, 2012)
Cerebral hypometabolism and abnormal levels of amyloid beta (Aβ), total (t-tau) and phosphorylated tau (ptau) proteins in cerebrospinal fluid (CSF) are established biomarkers of Alzheimer's disease (AD). We examined the agreement between these biomarkers in a single center study of patients with AD of severity extending over a wide range. Forty seven patients (MMSE 21.4±3.6, range 13-28 points) with incipient and probable AD underwent positron emission tomography with [18F]-fluorodeoxyglucose (FDG-PET) and lumbar puncture for CSF assays of Aβ1-42, p-tau181, and t-tau. All findings were classified as either positive or negative for AD. Statistical analyses were performed for the whole sample (n=47) and for the subgroups stratified as mild (MMSE >20 points, n=30) and moderate (MMSE <21 points, n=17) AD. In the whole patient sample, the agreement with the FDG-PET finding was 77% (chance-corrected kappa [κ]=0.34, p=0.016) for t-tau, 68% (κ=0.10, n.s.) for p-tau181, and 68% (κ=0.04, n.s.) for Aβ1-42. No significant agreement was found in the mild AD subgroup, while there was a strong agreement for t-tau (94%, κ=0.77, p=0.001) and p-tau181 (88%, κ=0.60, p=0.014) in the moderate AD group. A significant agreement between the FDG-PET and CSF tau findings in patients with AD supports the view that both are markers of neurodegeneration. CSF tau proteins and FDG-PET might substitute each other as supportive diagnostic tools in patients with suspected moderate-to-severe Alzheimer's dementia, while this is not the case in subjects at an earlier disease stage.
Keywords: tau